Pengaruh Strategi Keamanan Nasional Transformasional Jepang Terhadap Keamanan Regional Asia Timur - Karisma; Agussalim Burhanuddin; Ishaq Rahman (Journal of Peace, Security and Democracy, 2025)
The Transformation of Japan's National Security Strategy for 2022 is a form of Japan's defense and security policy which includes the National Security Strategy, National Defense Security and the Defense Development Program in East Asia. The type of research used in this research is qualitative with data obtained through literature studies from a number of books, journals and official documents that relate accurately to the problems studied. The results of this research show that the transformation policy of Japan's 2022 National Security Strategy triggers various responses from target countries. China responded by increasing the PLA and military modernization in the disputed Islands and Taiwan Strait. North Korea hints at a military attack in the form of nuclear and missiles if it threatens its fundamental policies. Russia carried out provocative actions based on joint military exercises and military bases on the Kuril Islands in dispute with Japan.